So I've been looking for a formula where I can input the parameter $k$ and it will give me a formula for $1^k+2^k+3^k...+ n^k$ with $n,k \in \mathbb{N}$. The result is always a polynomial with $k+1$ as highest power. I've taken the time to calculate the polynomes for $k=1$ to $k=10$ by hand and using the interpolation feature of Wolfram Alpha. Here are the results (I'll only show the coefficients for the sake of clarity. the coefficients are always from $n^{k+1}$ to $n^1$. the constant is always $0$. So $\frac{1}{2},-\frac{1}{2}$ becomes $\frac{1}{2}n^2-\frac{1}{2}n$):

  • $k=1$ : $\frac{1}{2},-\frac{1}{2}$
  • $k=2$ : $\frac{1}{3},\frac{1}{2},\frac{1}{6}$
  • $k=3$ : $\frac{1}{4},\frac{1}{2},\frac{1}{4},0$
  • $k=4$ : $\frac{1}{5},\frac{1}{2},\frac{1}{3},0,-\frac{1}{30}$
  • $k=5$ : $\frac{1}{6},\frac{1}{2},\frac{5}{12},0,-\frac{1}{12},0$
  • $k=6$ : $\frac{1}{7},\frac{1}{2},\frac{1}{2},0,-\frac{1}{6},0,\frac{1}{42}$
  • $k=7$ : $\frac{1}{8},\frac{1}{2},\frac{7}{12},0,-\frac{7}{24},0,\frac{1}{12},0$
  • $k=8$ : $\frac{1}{9},\frac{1}{2},\frac{2}{3},0,-\frac{7}{15},0,\frac{2}{9},0,-\frac{1}{30}$
  • $k=9$ : $\frac{1}{10},\frac{1}{2},\frac{3}{4},0,-\frac{7}{10},0,\frac{1}{2},0,-\frac{3}{20},0$
  • $k=10$ : $\frac{1}{11},\frac{1}{2},\frac{5}{9},0,1,0,1,0,-\frac{1}{2},0,\frac{5}{66}$

There are a few things i notice: Firstly, the coefficient of the highest power seems to be $\frac{1}{k+1}$. Secondly, the coefficient of the second highest power seems to be $\frac{1}{2}$ with the exception of $k=1$. Thirdly, all coefficients of the fourth, sixth, eight highest power and so on seem to be $0$. What is the formula that will output the coefficients for any value of $k$?


https://en.m.wikipedia.org/wiki/Faulhaber%27s_formula seems to deliver exactly what i needed. Original answer by MooS


I'll give you a derivation which I don't think is all that known. You just need to know four things:

(1) A version of the umbral Taylor series

Suppose that we have a sequence:


And we want to find the function of $n$ that defines $a_n$.

To do this we start by letting $a_{n+1}-a_n=\Delta a_n$ and we call this operation on $a_n$ the forward difference. Then given $\Delta a_n$ we can find $a_n$. Sum both sides of the equation from $n=0$ to $x-1$, and note that we have a telescoping series:

$$\sum_{n=0}^{x-1} \Delta a_n=\sum_{n=0}^{x-1} (a_{n+1}-a_n)=a_{x}-a_{0}$$

Hence $a_n=a_0+\sum_{i=0}^{n-1} \Delta a_i$. Also $\Delta a_n=\Delta (0)+\sum_{i=0}^{n-1} \Delta^2 a_n$...and so forth. Using this we must have if the series converges:

$$a_n=a_0+\Delta (0) \sum_{x_0=0}^{n-1} 1+\Delta \Delta (0) \sum_{x_0=0}^{n-1} \sum_{x_1=0}^{x_0-1} 1+\Delta \Delta \Delta (0) \sum_{x_0=0}^{n-1} \sum_{x_1=0}^{x_0-1} \sum_{x_2=0}^{x_1-1} 1+\cdots$$

Where $\Delta^i (0)$ denotes the first term ($n=0$) of the $i$ th difference sequence of $a_n$.

Through a combinational argument, If we take $\Delta^0 (0)=a_0$ and ${n \choose 0}=1$ we may get:

$$a_n=\sum_{i=0}^{\infty} \Delta^i(0) {n \choose i}$$

(2) Hockey stick identity Proof of the Hockey-Stick Identity: $\sum\limits_{t=0}^n \binom tk = \binom{n+1}{k+1}$

(3) The forward difference of a polynomial of degree $k$ is of degree $k-1$ (follows from binomial theorem) hence $k+1$ forward differences survey results in $0$ as $k$ forward differences must result in a constant sequence.

(4) A polynomial of degree $k$ can be uniquely defined by the sequence $f(0),f(1),f(2),...f(k)$.

Using (1), (2), (3), and (4) you may come up with the formula:

$$\sum_{s=1}^{n} s^k=\sum_{s=1}^{k} b_s{n+1\choose s+1}$$

By considering how to represent $a_s=s^k$ as a sum of multiples of binomials.

$$s^k=0+b_1{ s \choose 1}+b_2{s \choose 2}+\cdots+ b_k{s \choose k}+0+0+\cdots=\sum_{i=1}^{k} b_i{s \choose i}$$.
$$\sum_{s=1}^{n}\sum_{i=1}^{k} b_i{s \choose i}=\sum_{s=1}^{n}b_1{ s \choose 1}+\sum_{s=1}^{n}b_2{s \choose 2}+\cdots +\sum_{s=1}^{n}b_k{s \choose k}$$.
Taking the constants $b_1,b_2,...$ out of the sums and utilizing the hockey stick identity we get our desired result.

Now see Function $f: \mathbb{Z} \to \mathbb{Z}^n$ related to $\sum_{k=1}^{x} k^n$.

We have that:


Where ! denotes the factorial and $S( , )$ denotes the stirling numbers of the second kind.

Hence we have that:

$$\sum_{s=1}^{n} s^k=\sum_{s=1}^{k} s!S(k,s){n+1 \choose s+1}$$

Here are some examples.


$$\sum_{s=1}^{n} s^1=1{n+1 \choose 2}$$



$$\sum_{s=1}^{n} s^2=1{n+1 \choose 2}+2{n+1 \choose 3}$$



$$\sum_{s=1}^{n} s^3=1{n+1 \choose 2}+6{n+1 \choose 3}+6{n+1 \choose 4}$$


  • $\begingroup$ See this math.stackexchange.com/questions/1848443/… if you want a proof the series I wrote describing $a_n$ in closed form (the series I introduced in my question: also some form of the umbral Taylor series) let me know. A long time ago I discovered it on my own by trying to solve a series of recurrence relations of the form $f(x+1)-f(x)=g(x)$ using telescoping sums. $\endgroup$ – Ahmed S. Attaalla Aug 2 '16 at 13:27
  • 1
    $\begingroup$ Nice to see an Arabic name. Good luck Ahmed. $\endgroup$ – Zaid Alyafeai Aug 4 '16 at 18:37

Another way to derive a formula for $$S(k,n)=\sum_{s=1}^{n}{s^k}$$ is to use the binomial expansion. To do this, you can start by changing the summation index $s$ to $t+1$. That is:$$S(k,n)=\sum_{t=0}^{n-1}{(t+1)^k}=1+\sum_{t=1}^{n-1}{(t+1)^k}$$Using binomial expansion we have:$$S(k,n)=1+\sum_{t=1}^{n-1}{\sum_{j=0}^{k}{\binom{k}{j}t^j}}$$Changing the order of summation (notice the independence) gets:$$S(k,n)=1+\sum_{j=0}^{k}{\sum_{t=1}^{n-1}{\binom{k}{j}t^j}}=1+\sum_{j=0}^{k}{\left(\binom{k}{j}\sum_{t=1}^{n-1}{t^j}\right)}$$The inner sum equals $S(j,n-1)$, so: $$S(k,n)=1+\sum_{j=0}^{k}{\binom{k}{j}S(j,n-1)}$$Now, by excluding the last two terms of the summation (the terms obtained by $j=k-1$ and $j=k$) we finally get: $$S(k,n)=1+S(k,n-1)+kS(k-1,n-1)+\sum_{j=0}^{k-2}{\binom{k}{j}S(j,n-1)}$$ Since $S(k,n)-S(k,n-1)=n^k$: $$S(k-1,n-1)=\frac{1}{k}\left(n^k-1-\sum_{j=0}^{k-2}{\binom{k}{j}S(j,n-1)}\right)$$ The formula shows a recursive relation between $S(k-1,n-1)$ and lower sums, i.e., $S(0,n-1),S(1,n-1),\dots,S(k-2,n-1)$. By changing $k$ to $k+1$ and $n$ to $n+1$ the original format emerges: $$S(k,n)=\frac{1}{k+1}\left((n+1)^{k+1}-1-\sum_{j=0}^{k-1}{\binom{k+1}{j}S(j,n)}\right)$$ You can now start from $S(0,n)=n$ and derive $S(k,n)$ for $k=1,2,\dots$. For example: $$S(1,n)=\frac{1}{2}\left( (n+1)^2-1-\binom{2}{0}S(0,n)\right)=\frac{1}{2}\left( n^2+2n+1-1-n \right)=\frac{1}{2}n(n+1)$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.